Creating the Economics Digital Classroom in a New Zealand Secondary School – a Case Study - Sharma, Shraddha (Auckland University of Technology, 2016)
Secondary schools in New Zealand are incorporating the use of digital technologies, and reflecting this implementation in their school’s statements of vision, mission and strategic intent. As this initiative is widely promoted by the Ministry of Education, there is a need to examine the issues related to the process of digital technology implementation. This study has done that. The main purpose of this study therefore was specifically to investigate the issues digital technologies in Economics create for teachers, students and leaders, and to examine the critical role of school leadership in creating the economics digital classroom. This information provides insight into the current state of pedagogical approaches applied by teachers and also how the affordances of digital technologies help improve student learning in Economics in a New Zealand secondary school. The ways in which the digitisation of educational practices exercises the leadership skills and expertise of teachers and students, supporting them to promote quality learning was also assessed. A case study approach was used to answer the research question. Qualitative methods, including semi-structured interviews and focus group was used to collect data. The qualitative data was collected from the HOD Economics (and sole teacher of Economics) and the Deputy Principal of one case study school. A focus group of Year 11 Economics students was recruited. The research revealed that leaders and teachers’ digital technology adoption of digital technology in learning and teaching at the school was low and superficial. Teachers used digital technology as an add-on tool and their practices remained teacher-centred. Teachers perceived they used digital technologies in their classroom but very few actually did. The study also found that the use of digital technology in professional development was similarly superficial. Teachers attending professional development were reluctant to embrace digital technologies due to the school’s current priorities of delivering examination results, and their lack of time due to time spent in preparing and marking hand written assessments. The school did not have proper channels to measure the impact of digital technologies effectively in school. The literature showed, however, that there are possibilities, but also challenges in setting up an Economics classroom. The findings confirm those reported in the literature that inefficient leadership, management, inadequate resources and teacher motivation influence the development of economics digital classrooms.
Keywords: Affordance; digital pedagogy; Economics digital classroom; school leadership